The Boy who cried wolf. -- (Makati city, Philippines : Straight Lines International, Inc., 2001)
A boy tending sheep on a lonely mountainside thinks it a fine joke to cry "wolf" and watch the people come running--and then one day a wolf is really there, but no one answers his call.
Keywords: Fables; Folklore